INTRODUÇÃO AO NÚMERO ESPECIAL / INTRODUCTION TO THE SPECIAL NUMBER - da Costa, Nuno Marques; da Costa, Eduarda Marques; Marafon, Glaucio José (Geo UERJ, 2017)
doi:10.12957/geouerj.2017.29944 INTRODUÇÃO AO NÚMERO ESPECIAL / INTRODUCTION TO THE SPECIAL NUMBER